2017
DOI: 10.1037/cdp0000152
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to White religious iconography influences Black individuals’ intragroup and intergroup attitudes.

Abstract: Although there are many contributing factors to explain why Black adults and children may internalize anti-Black attitudes, the potential role religion may play in such processes-specifically the exposure to White religious iconography-cannot be ignored. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 46 publications
2
14
1
Order By: Relevance
“…cause shifts in racial and gender prejudice (Howard et al, 2018;Howard & Sommers, 2017. Interestingly, we did not find evidence that beliefs about Jesus race predicted individuals' implicit racial associations.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…cause shifts in racial and gender prejudice (Howard et al, 2018;Howard & Sommers, 2017. Interestingly, we did not find evidence that beliefs about Jesus race predicted individuals' implicit racial associations.…”
Section: Discussioncontrasting
confidence: 86%
“…More recently, the relationship between Christianity and racial prejudice has been documented experimentally using priming techniques (e.g., Howard & Sommers, 2017, 2019; Johnson et al, 2010). For example, Johnson et al (2010) found that priming individuals with Christian concepts caused increases in both individuals’ explicit and subtle anti-Black attitudes.…”
Section: Relationship Between Christianity and Prejudicementioning
confidence: 99%
“…We controlled for multiple ideologies (e.g., religiosity, conservatism, racial prejudice, sexist attitudes), recruited diverse participant groups (e.g., Black, White, male, female, adult, child, Christian, atheist), and considered both Christian and novel contexts, and consistently found evidence to suggest that attributing a social identity to God is another route by which religiosity predicts group-based prejudice. These data build on the recent finding that exposure to religious iconography predicts pro-White and anti-Black prejudice (Howard & Sommers, 2017, 2019), to demonstrate further and for the first time that attributing a social identity to God predicts widespread, early emerging, and intuitive conceptions of who deserves to rule.…”
Section: Discussionsupporting
confidence: 66%
“…Unlike other areas of psychology, where masking of faces and images is possibly the predominant technique for exploring subliminal processing (see, for example, van der Ploeg et al, 2017), morality and religiosity have been explored using masked or primed image stimuli only in a handful of studies. These few studies used non-morality related masked image primes and focused on whether these primes can induce disgust sensitivity (Preston, Ritter & Ivan Hernandez, 2010), political and secular conservatism (Samuel, 2016), whether the primes associated with developmental attachment (Birgegard & Granqvist, 2004), racial prejudice (Howard & Sommers, 2017), the regulation of negative emotion (Harenski, & Hamann, 2006) and moral and immoral attitudes as personality traits (Luo et al, 2006; see also Garrigan, Adlam & Langdon, 2016).…”
Section: Introductionmentioning
confidence: 99%